Respuesta :

Answer:

(x - 4)² - 11

Step-by-step explanation:

Given

x² - 8x + 5

To obtain the required form use the method of completing the square.

add/subtract ( half the coefficient of the x- term)² to x² - 8x

= x² + 2(- 4)x + 16 - 16 + 5

= (x - 4)² - 11

Answer:

[tex](x-4)^{2}-11[/tex]

Step-by-step explanation:

x² - 8x + 5 = x² - 8x + (16 - 16) + 5      {we just added 16 and subtractEd it }

                 = (x - 4)² - 16 + 5               {Reason :  x² - 8x + 16 = (x - 4)² }

                 = (x - 4)² - 11

ACCESS MORE